Efficacy and Safety in the Continued Treatment With a Biosimilar Drug in Patients Receiving Infliximab: A Systematic Review in the Context of Decision-Making From a Latin-American Country - Mezones-Holguin, Edward; Gamboa-Cardenas, Rocio Violeta; Sanchez-Felix, Gadwyn; Chávez-Corrales, José; Helguero-Santin, Luis Miguel; Laban Seminario, Luis Max; Burela-Prado, Paula Alejandra; Castro-Reyes, Maribel Marilu; Fiestas, Fabian (Frontiers in Pharmacology, 2019)
Introduction: Biological products, including infliximab, are a therapeutic option for various medical conditions. Biosimilars are a safe, effective and approved alternative for these conditions in affiliated patients to start treatment with Infliximab. However, there is a group of patients who receive treatment with the biological reference products (PBR), in whom the possibility of continuing their therapeutic regimen with a biosimilar biological product (PBB) must be assessed. Methodology: We conducted a systematic review of controlled randomized studies regarding the continuation of biosimilar therapy in patients receiving the original Infliximab under the approved conditions of use for EsSalud. We performed search in Pubmed-MEDLINE, SCOPUS, WOS, EMBASE, TRIPDATABASE, DARE, Cochrane Library, NICE, AHRQ, SMC, McMaster-PLUS, CADTH, y HSE until June 2018. We use the Cochrane tool to assess the risk of bias. Results: A total of 1136 records were identified in the primary search, we removed 337 duplicates. From the 799 screened records, we excluded 785. Of the 14 documents evaluated in full text, we included five Clinical Trials. The PBR CTP-13 was evaluated in four studies, while the remaining research evaluated the biosimilar SB2. Two trials were double-blind and reported no differences in terms of efficacy and safety in patients who switched from PBR to PBB versus those who maintained treatment with PBR for all medical conditions evaluated (CTP-13) and for rheumatoid arthritis. While the three remaining studies were an extension to open label primary clinical trials in which no differences were reported in terms of efficacy and safety in people who initially received the PBR and switched to a biosimilar, compared to those who maintained their treatment with PBB. Conclusions: Outside of the limitations of the primary studies included, the evidence shows that there were no differences regarding the net benefit of continuing the treatment with the original Infliximab or exchanging its biosimilar component in terms of efficacy and safety. Based on the opportunity cost principle, the exchange of a biosimilar in patients receiving the original Infliximab is a valid therapeutic alternative with a good efficacy and safety profile.